Ethical Evaluation of Learning Organizations: A Conceptual Framework - Costa, Gonçalo Jorge Morais da (2014)
A key assumption for recognizing knowledge society is the existence of learning organizations. As a result, literature has been fruitful in engaging a wide debate concerning its characteristics, dimensions, evolution, evaluation procedures, or ethical behaviour. Likewise, it is interesting to denote that research appears to pay little regard to the impacts of existing ethical and social dilemmas about knowledge creation, retention/use and sharing within organizational contexts. Therefore, the key purpose of this manuscript is to present a conceptual framework that denotes these dilemmas and their impacts in organizational strategy.For that, this contribution resumes an ongoing research project which intends to approach ethical and social dilemmas in learning organizations. Moreover, it suggests that these dilemmas impact on organizational strategy, as well as that existing evaluation models for learning organizations do not promote the ethical evaluation.